Association Between Screen Overuse and Behavioral and Emotional Problems in Elementary School Children - Choi, Yeonkyu; Lee, Dong Yun; Lee, Sangha; Park, Eun-Jin; Yoo, Hee Jeong; Shin, Yunmi (Journal of korean Academy of Child and Adolescent Psychiatry, 2021)
This study identified the association between excessive exposure to screen media and behavioral and emotional problems in elementary school students. A total of 331 parents of children aged 7-10 years were recruited from "The Kids Cohort for Understanding of Internet Addiction Risk Factors in Early Childhood (K-CURE)" study. Children's demographics, household media ownership, screen time, and behavioral/emotional problems were assessed using a parental questionnaire. Children's behavior/emotional problems were measured using the Korean version the of Child Behavior Checklist (K-CBCL) score. The total K-CBCL score in the screen overuse group was 51.18±9.55, significantly higher than 47.28±10.09 in the control group (t=2.14, p=0.05). For each subscale, the externalization score (51.65±10.14, 48.33±8.97, respectively; t=2.02, p<0.05), social problem score (55.41±6.11, 53.24±5.19, respectively; t=2.27, p<0.05), and rule breaking behavior score (55.71±6.11, 53.24±5.19, respectively; t=2.27, p<0.05) were significantly higher in the screen overuse group than in the control group. In addition, the screen overuse group also had a significantly higher usage rate than the control group, even if limited to smartphones, not only on weekdays (3.56±2.08, 1.87±2.02, respectively; t=-4.597, p<0.001) but also weekends (1.62±0.74, 1.19±0.83, respectively; t=-3.14, p=0.003). The study suggested that screen media overuse patterns in children in Korea are particularly relevant to the excessive use of smartphones and are related to higher risks of emotional and behavioral problems.